Ticagrelor Versus Clopidogrel in Black Patients With Stable Coronary Artery Disease. (July 2015) - Waksman, Ron; Maya, Juan; Angiolillo, Dominick J.; Carlson, Glenn F.; Teng, Renli; Caplan, Richard J.; Ferdinand, Keith C.
<x xml:space="preserve">Abstract</x> Background— The burden of coronary artery disease (CAD) is high in blacks, highlighting the need for clinical research of antiplatelet agents in this population. We sought to evaluate platelet reactivity during loading and maintenance dosing of ticagrelor versus clopidogrel, and the pharmacokinetic profile of ticagrelor and its metabolite AR-C124910XX, in black patients with stable CAD taking low-dose aspirin (acetylsalicylic acid). Methods and Results— In a multicenter, randomized, open-label, crossover study, 34 blacks with stable CAD receiving acetylsalicylic acid 75 to 100 mg/d were randomized to clopidogrel (600 mg, then 75 mg QD for 7–9 days) or ticagrelor (180 mg, then 90 mg BID for 7–9 days). After washout 10 to 14 days, patients switched regimens. The primary end point was platelet reactivity 2 hours post loading dose (P2Y12 reactivity units [PRU] measured by the VerifyNow assay). Least-squares mean PRU at 2 hours post loading dose was lower with ticagrelor (27.6) versus clopidogrel (211.2); least-squares mean difference was –183.6 (95% confidence interval, –213.9 to –153.3; P<0.001). At all time points, the least-squares mean PRU was significantly lower, and the percent reduction in PRU from baseline was statistically greater, with ticagrelor versus clopidogrel. At 2 hours post dose, the prevalence of high on-treatment platelet reactivity (≥208 PRU) was lower with ticagrelor (0%) than with clopidogrel (57.1%). Pharmacokinetic profiles of ticagrelor and AR-C124910XX were consistent with previous reports in stable CAD populations. Conclusions— In black patients with stable CAD receiving low-dose acetylsalicylic acid, ticagrelor provided a faster onset and greater degree of platelet inhibition than clopidogrel. Clinical Trial Registration— URL: http://www.clinicaltrials.gov. Unique identifier: NCT01523392.